2014
DOI: 10.1103/physrevb.90.054111
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically stable lithium silicides and germanides from density functional theory calculations

Abstract: High-throughput density-functional-theory (DFT) calculations have been performed on the Li-Si and Li-Ge systems. Lithiated Si and Ge, including their metastable phases, play an important technological rôle as Liion battery (LIB) anodes. The calculations comprise structural optimisations on crystal structures obtained by swapping atomic species to Li-Si and Li-Ge from the X-Y structures in the International Crystal Structure Database, where X={Li,Na,K,Rb,Cs} and Y={Si,Ge,Sn,Pb}. To complement this at various Li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 79 publications
8
114
0
2
Order By: Relevance
“…47,48 AIRSS has successfully predicted the structures of phases of Li-ion batteries (LIBs) containing sulfur, 49 phosphorus, 50 silicon, and germanium. 51 Not limited to ground-state crystal structures, AIRSS has been used to understand point defects 52 and continuous phase transitions in LIBs. 53 AIRSS searches were carried out on stoichiometries of Li x Mo y S 2 y at ratios of less than of 8:1 of Li:MoS 2 which corresponds to a theoretical capacity of up to 1688 mAh/g.…”
Section: Methodsmentioning
confidence: 99%
“…47,48 AIRSS has successfully predicted the structures of phases of Li-ion batteries (LIBs) containing sulfur, 49 phosphorus, 50 silicon, and germanium. 51 Not limited to ground-state crystal structures, AIRSS has been used to understand point defects 52 and continuous phase transitions in LIBs. 53 AIRSS searches were carried out on stoichiometries of Li x Mo y S 2 y at ratios of less than of 8:1 of Li:MoS 2 which corresponds to a theoretical capacity of up to 1688 mAh/g.…”
Section: Methodsmentioning
confidence: 99%
“…66 CSP on varying stoichiometries has also impacted energy materials research, with Li 7 Ge 3 being predicted 67 and then found in research on germanium anodes in lithium batteries.…”
mentioning
confidence: 99%
“…In general, the emergence of amorphous of Li-Ge alloys has played a crucial role to provide Li-storage capability during discharge/charge [49][50][51] [52]. The conversion between crystalline and amorphous Ge was believed to occur by virtue of amorphous Li 9 Ge 4 [49] or Li 15 Ge 4 [53] during Li-cycling.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(3)-(6). Because of the formation of electrochemically amorphous active materials (Curve 1 inFigure 6c) in the charge stage[49][50][51]57], it is very difficult to discriminate the exact crystal phases of the charged materials with conventional XRD technique. As a beneficial reference, we have annealed the active materials at N 2 atmosphere for 30 minutes in the hope of crystallizing the amorphous substances (Curve 2, 3 inFigure 6cand ESI).…”
mentioning
confidence: 99%